RANCANGAN STRATEGI LEMBAGA FARMASI TNI AL DALAM MEMASUKI PASAR FARMASI NASIONAL: Rancangan Strategi Lembaga Farmasi TNI AL Dalam Memasuki Pasar Farmasi Nasional - Ruskar, Dandung; Kumala, Shirly; Noor, Laili Savitri (PendIPA Journal of Science Education, 2025)
The growth of the pharmaceutical market in Indonesia provides a positive trend. It is increasing along with the increase in population, public awareness of health, and people's purchasing power. Supported by the government's seriousness to improve services in the health sector, making the pharmaceutical industry one of the priority non-oil and gas industries and included in the National Industrial Development Master Plan (RIPIN) 2015-2035. This positive market growth is in stark contrast to the current growth of the pharmaceutical industry. According to data from the Central Statistics Agency (BPS), the pharmaceutical industry in Indonesia has experienced very slow growth, namely by 0.7% in 2022 and by 0.1% in 2023. The ASEAN Summit in September 2023 also placed Indonesia as a country with the lowest score for the availability of medicines. The Navy Pharmaceutical Institute (Lafial) as a pharmaceutical industry owned by the Navy has great potential to be utilized. Moreover, Lafial's current condition requires increasing production capacity to get other budgets apart from the state budget by participating in the Indonesian pharmaceutical market. This research aims to obtain a business strategy for Lafial to be able to participate in the Indonesian pharmaceutical market and despite the current less conducive conditions. This research uses SWOT analysis as a method which is then followed by using the QSPM matrix. This research is a qualitative descriptive analysis to explore the components of internal and external factors owned by Lafial. The data used are data obtained from interviews, FGDs, questionnaires, and secondary data. This study provides results on the strength component score value of 1.50; the weakness component is 1.98; the opportunity component is 2.08 and the threat component is 1.67. With these results, Lafial's position is in quadrant III of the SWOT quadrant. A strategy analysis using QSPM gave the result that the market switch strategy by improving other functions other than production gave the highest TAS value of 5.05. The second strategy is increasing production capacity through toll manufacturing activities with a TAS value of 4.89. The third strategy is building cooperation with the TNI Navy cooperative with a TAS value of 4.81 and the last strategy is to transform into a sub-task force that can deposit PNBP with a TAS value of 4.22.